Straits settlements ordinance 1867-1941 [1867-1889] (Petalaing Jaya : Arkib Negara)
Mengandungi akta-akta dan ordinan-ordinan bagi tahun 1867-1889 seperti Act no. 1 of 1867 - Government Officers Appointment (1st April 1867]; Act no. II of 1867 - Executory Poers (1st April 1867); Act No. III Naturalization [15th May 1867] ; Ord. No. IV of 1871 Registration of Deeds (9th Jun 1871);Ord. no IV. of 1871 The Penal Code; Ord. no. VIII Locomotive (6th Noc 1871); Ord. no. I of 1872 Police Force (4th Jul. 1872); Ord. No. IV 1872 Convicts' Offences (16th Sept. 1872); Ord. no. 1 of 1873 Foreign Seamen's Offences (20th May 1873]; Ord. no. VII Court Suitors' Deposit Transfer (11th May 1874); Ord. no. II of 1876 Presbyterian Church (24 March 1876]; Ord. no. IV of 1876 State Prisoners (27 March 1876); Ord. no. IV 1877 - Imperial Extradition (7th Sept. 1877);Ord. no. VI of 1877 Ex Sultan Abdullah of Perak (2nd Apr. 1877); Ord. no. 1 of 1878 Synagogue (29 March 1878).